Status Hukum Kegiatan Pertambangan Pada Lahan Perkebunan Masyarakat Di Atas Hak Guna Usaha Ditinjau Dari Undang-Undang Pokok Agraria - Iskandar Marto A.M Papeo; Mutia Cherawaty Thalib; Nurul Fazri Elfikri (Journal of Contemporary Law Studies, 2026)
Land conflicts in Indonesia frequently arise due to overlapping land use between local communities and holders of Right to Cultivate (Hak Guna Usaha/HGU), particularly in mining activities conducted on plantation land. This issue creates legal uncertainty and the potential for prolonged disputes. This study aims to analyze the legal status of community mining activities carried out on land under HGU and its regulation under the Basic Agrarian Law and related legislation. The research employs a normative legal method using statutory and conceptual approaches, relying on primary, secondary, and tertiary legal materials analyzed qualitatively. The findings indicate that mining activities on HGU land may only be conducted upon obtaining permits from the competent authorities and the consent of the land rights holder. However, in practice, overlapping land use frequently occurs due to weak coordination in licensing, unclear land status, and lack of transparency in land administration. This condition may lead to unlawful acts and cause losses to the parties involved. Therefore, it is necessary to strengthen an integrated, transparent, and accountable licensing system to ensure legal certainty and justice in the management of agrarian resources.